2021
DOI: 10.24820/ark.5550190.p011.404
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole-carboxaldehydes as versatile precursors for different pyrazole-substituted heterocyclic systems

Abstract: In the last decade, interest in pyrazole chemistry has grown considerably due to the discovery of fascinating properties demonstrated by a large number of pyrazole derivatives. They occur in a wide range of natural products, dyes, and as scaffolds in a number of drugs and associated pharmaceutical active substances. Substantial attention has been paid to the creation of hybrid molecules in which two heterocycles are bound in a single molecule to enhance their biological effectiveness and overcome drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…For example, A. Domling's group synthesized 1-(1H-tetrazol-5-yl)imidazo [1,5-a]pyridines via a one-pot reaction of pyridine-2-carboxaldehyde, an amine reactant, isocyanides, and azidotri(methyl)silane [24]. Pyrazole-4-carbaldehydes are very useful building blocks in organic synthesis [25][26][27]. For example, Sivaprasad and Peramal reported the Biginelli coupling reaction of 3-aryl-1-phenyl-1Hpyrazole-4-carbaldehydes with ethyl acetoacetate and urea in the presence of phosphotungstic acid to give 4-(3-aryl-1-phenyl-4-pyrazolyl)-1,2,3,4-tetrahydropyrimidin-2-ones [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, A. Domling's group synthesized 1-(1H-tetrazol-5-yl)imidazo [1,5-a]pyridines via a one-pot reaction of pyridine-2-carboxaldehyde, an amine reactant, isocyanides, and azidotri(methyl)silane [24]. Pyrazole-4-carbaldehydes are very useful building blocks in organic synthesis [25][26][27]. For example, Sivaprasad and Peramal reported the Biginelli coupling reaction of 3-aryl-1-phenyl-1Hpyrazole-4-carbaldehydes with ethyl acetoacetate and urea in the presence of phosphotungstic acid to give 4-(3-aryl-1-phenyl-4-pyrazolyl)-1,2,3,4-tetrahydropyrimidin-2-ones [28].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we reviewed the usefulness of pyrazole-4-carbaldehydes as versatile precursors for different pyrazole-substituted heterocyclic systems. 52 Heterocyclic compounds mentioned in this review are arranged based on the size of the heterocyclic ring as well as the position and number of the heteroatoms. 53 reported that heating of 3-aryl-1-phenyl-1H-pyrazol-4-carbaldehydes 1 with ethyl azidoacetate 2 in ethanol followed by heating in toluene at reflux gave pyrrolo [2,3-c]pyrazole derivatives 3a and 3b in 30 and 35% yield, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%